2015
DOI: 10.1016/j.fct.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Polyester monomers lack ability to bind and activate both androgenic and estrogenic receptors as determined by In Vitro and In Silico methods

Abstract: The paper presents results from the screening of seven monomers used by Eastman Chemical to make various polymers. Ethylene glycol, diethylene glycol, polytetramethylene glycol, isophthalic acid, monosodium-5-sulfoisophthalic acid, 1,4-cyclohexanedicarboxylic acid, and dimethylcyclohexanedicarboxylate were screened for potential androgenicity or estrogenicity. The following studies were conducted: QSAR for binding to the AR and ER, in vitro Androgen Receptor Binding Assay, in vitro Estrogen Receptor Binding As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the first time AA-DEG-IPA-DEG and AA-DEG have been tested for ability to interfere with AR, AhR, and TTR. However, the monomers DEG and IPA have been tested for AR binding both in silico and in vitro, as well as in an AR transactivation assay, but exhibited no effect (Osimitz, Welsh, Ai, & Toole, 2015). These findings could suggest that the AA moiety of the compounds play a role in the observed antiandrogenic activities.…”
Section: In Vitro Endocrine Assaysmentioning
confidence: 99%
“…To our knowledge, this is the first time AA-DEG-IPA-DEG and AA-DEG have been tested for ability to interfere with AR, AhR, and TTR. However, the monomers DEG and IPA have been tested for AR binding both in silico and in vitro, as well as in an AR transactivation assay, but exhibited no effect (Osimitz, Welsh, Ai, & Toole, 2015). These findings could suggest that the AA moiety of the compounds play a role in the observed antiandrogenic activities.…”
Section: In Vitro Endocrine Assaysmentioning
confidence: 99%
“…Other BPA replacements, such as CBDO, CHDM, and DMT monomer, had been demonstrated with no binding affinity to ER or AR by the ligand binding assay and reporter gene assay. , However, the cell proliferation assay showed that CHDM and DMT worked as the agonist on ER in MCF-7 cells . CHDM increased the secretion of E2 in H295R cells .…”
Section: Evaluation Of Endocrine Disruptionmentioning
confidence: 99%
“…If the test compound disrupts the endocrine system via alternation of hormone production, the ligand binding assay and reporter gene assay will provide a false negative result. One example is that CHDM and TPA show no androgenic and estrogenic activity with ligand binding and reporter gene assays 76 but show endocrine disruption activity with the steroidogenesis assay and decreased reproduction with in vivo tests. 77 With regard to throughput, the reporter gene assay usually takes about 1 day to perform, while the cell proliferation and steroidogenesis assay takes several days of incubation.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%